2016
DOI: 10.1002/jso.24406
|View full text |Cite|
|
Sign up to set email alerts
|

The American Society of Peritoneal Surface Malignancies Multi-Institution evaluation of 1,051 advanced ovarian cancer patients undergoing cytoreductive surgery and HIPEC: An introduction of the peritoneal surface disease severity score

Abstract: PSDSS was capable of identifying a better surviving patient population in advanced-stage OEC. While randomized trials to evaluate the benefit of HIPEC are needed, the PSDSS may be a useful tool for selecting and stratifying OEC patients in clinical trials. J. Surg. Oncol. 2016;114:779-784. © 2016 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In general, for patients with colorectal, ovarian, high-grade appendix, and mesothelial tumors, selecting patients with a peritoneal carcinoma index score of less than 25 is important in achieving long-term survival. 27 , 28 , 29 , 30 , 31 , 32 This also enables surgeons performing CRS/HIPEC to achieve optimal surgical cytoreduction, which is paramount in and predictive of long-term survival. 29 Additionally, surgeons who perform CRS/HIPEC in the United States are a small community who primarily perform these procedures at high-volume centers because only a limited number of institutions and medical centers are equipped or willing to invest in a CRS/HIPEC program.…”
Section: Discussionmentioning
confidence: 99%
“…In general, for patients with colorectal, ovarian, high-grade appendix, and mesothelial tumors, selecting patients with a peritoneal carcinoma index score of less than 25 is important in achieving long-term survival. 27 , 28 , 29 , 30 , 31 , 32 This also enables surgeons performing CRS/HIPEC to achieve optimal surgical cytoreduction, which is paramount in and predictive of long-term survival. 29 Additionally, surgeons who perform CRS/HIPEC in the United States are a small community who primarily perform these procedures at high-volume centers because only a limited number of institutions and medical centers are equipped or willing to invest in a CRS/HIPEC program.…”
Section: Discussionmentioning
confidence: 99%
“…Only one study has examined the use of the PSDSS in a population of OC patients with peritoneal carcinomatosis . In this multi‐institutional study, the prognostic value of the PSDSS was evaluated retrospectively in 553 patients with epithelial OC who received CRS/HIPEC.…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane review on the use of intraperitoneal (ip) chemotherapy for primary OC [58] concluded that this treatment prolonged PFS and OS. While there is evidence of a survival benefit for IP chemotherapy/HIPEC after cytoreductive surgery in primary disease, there are fewer reports on its use and efficacy in recurrent disease [59]. No mention was made of this type of treatment in the Cochrane review on recurrent ovarian cancer [60] nor in the review by the Fifth Ovarian cancer Consensus Conference of the Gynecologic Cancer InterGroup [7].…”
Section: Surgery and Ip/hipec Chemotherapy For Recurrent Ovarian Cancermentioning
confidence: 99%